Self within marriage : the foundation for lasting relationships - Zeitner, Richard M. (Routledge, 2011)
Self Within Marriage combines the theoretical orientations of object-relations theory, self psychology, and systems theory as a way of understanding and working with couples and individuals whose relationship and emotional difficulties have centered on the common conundrum of balancing individuality and intimacy. Based on detailed case examples and couple therapy techniques, Self Within Marriage provides individual and couple therapists with a refreshing new framework for working with clients and for helping them understand who they are as individuals and as partners.